Implement routing protocols for VANET in a one-way environment - Mohammed D.; Mansor M.B.; Hock G.C. (American Institute of Physics Inc., 2024)
In recent years, a dedicated vehicular ad hoc network has gained significant interest and is an emerging field of research due to its contribution to the design of intelligent transportation systems. Wireless communication technologies such as (IEEE 802.11P) and (IEEE 1609 WAVE) aid in the transmission of messages from vehicle to infrastructure and vehicle to vehicle in the VANET. In VANET, orienting in an urban setting is a difficult challenge. One of the key issues in a VANET is designing a routing protocol, which aids in the delivery of reliable and efficient packets from node to node. Two types of routing protocols are employed in this study for VANET: Ad-hoc on-Demand Distance Vector and Maximum Distance on-Demand Routing Algorithm. The goal of this study is to compare the performance of the AODV and MDORA protocols in terms of packet delivery ratio and end-to-end delay in the case of vehicle movement at variable velocities ranging from (40-120 km/h) in one direction, with the simulation taking place in two environments with different vehicle density. The MATLAB software was used to analyze the performance of the routing protocols for the VANET. The MDORA protocol outperforms AODV in terms of end-to-end delay and packet delivery ratio, according to the simulation results. 2023 American Institute of Physics Inc.. All rights reserved.